2011
DOI: 10.1242/dev.069856
|View full text |Cite
|
Sign up to set email alerts
|

Fez function is required to maintain the size of the animal plate in the sea urchin embryo

Abstract: SUMMARYPartitioning ectoderm precisely into neurogenic and non-neurogenic regions is an essential step for neurogenesis of almost all bilaterian embryos. Although it is widely accepted that antagonism between BMP and its inhibitors primarily sets up the border between these two types of ectoderm, it is unclear how such extracellular, diffusible molecules create a sharp and precise border at the single-cell level. Here, we show that Fez, a zinc finger protein, functions as an intracellular factor attenuating BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 51 publications
(79 reference statements)
1
48
0
Order By: Relevance
“…Based on the expression patterns of six3 and foxq2 at the mesenchyme blastula stage (24 hpf ) and the fact that FoxQ2 acts as a cardinal regulator of many cell fates in the central ANE territory (Yaguchi et al, 2012(Yaguchi et al, , 2011(Yaguchi et al, , 2010, we reasoned that FoxQ2 might play a crucial role in establishing the inner and outer ANE domains. To test this hypothesis, we monitored the expression of six3 at the mesenchyme blastula stage in embryos injected with FoxQ2 morpholino oligonucleotides.…”
Section: Two Concentric Ane Territoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the expression patterns of six3 and foxq2 at the mesenchyme blastula stage (24 hpf ) and the fact that FoxQ2 acts as a cardinal regulator of many cell fates in the central ANE territory (Yaguchi et al, 2012(Yaguchi et al, , 2011(Yaguchi et al, , 2010, we reasoned that FoxQ2 might play a crucial role in establishing the inner and outer ANE domains. To test this hypothesis, we monitored the expression of six3 at the mesenchyme blastula stage in embryos injected with FoxQ2 morpholino oligonucleotides.…”
Section: Two Concentric Ane Territoriesmentioning
confidence: 99%
“…In the sea urchin embryo, six3 and foxq2 are the first ANE regulatory genes expressed in the presumptive ectoderm and both transcription factors act as cardinal regulators of ANE territory specification (Wei et al, 2009;Yaguchi et al, 2008Yaguchi et al, , 2011Yaguchi et al, , 2010. Similar to other deuterostome embryos, six3 and foxq2 initially exhibit pan-ectodermal expression, but then their expression is progressively restricted to a territory around the anterior pole (Wei et al, 2009;Yaguchi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2E–H, asterisk). Next, we compared distributions of zfhx1/z81 and fez , forebrain embryonic zinc finger , which we recently reported as being expressed in the entire animal plate during blastula stages and subsequently in serotonergic neurons and their precursors (Yaguchi et al, 2011). When the blastula-stage expression of fez begins to fade and is progressively replaced by stronger signals in a few individual cells in the animal plate region at mid-gastrula stage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that SoxC cells co-express Delta (Wei et al, 2016) and that treatment with DAPT, an inhibitor of Notch signaling, or a Delta morpholino results in the formation of clusters of neurons Wei et al, 2009;Yaguchi et al, 2011). This suggests that Notch signaling occurs subsequent to the final cell division and that the division is asymmetric, at least in the distribution of molecular components.…”
Section: Discussion the Model Of Neurogenesis In The Sea Urchinmentioning
confidence: 99%